Improving Bagasse Fly Ash Immobilized with Spirulina sp. as a Biosorbent for Fe3+ Elimination from Wastewater in Physical Chemistry Laboratories - Wahyuningsih, Sri; Sudarni, Dyan Hatining Ayu; Trisnawati, Ade; Nurjanah, Rima (Agroindustrial Technology Journal, 2026)
This work examined how to improve Bagasse Fly Ash (BFA) as an adsorbent by immobilizing it with Spirulina sp. biomass to remove Fe³⁺ ions from effluent from physical chemistry laboratories. A common silica-rich agroindustrial by-product, BFA has a porous structure but little capacity for adsorption because there aren't many active functional groups. On the other hand, although Spirulina sp. has a lot of amino, hydroxyl, carboxyl, phosphate, and sulfate groups that allow for strong interactions with metal ions, its low mechanical stability and challenging post-treatment separation limit its direct application. Spirulina was immobilized in a sodium silicate matrix made from BFA using the sol-gel technique in order to get around these problems. This produced a composite that combined the chemical activity of the biomass with the structural benefits of BFA. FT-IR characterization revealed structural changes upon immobilization and verified the existence of functional groups in charge of metal binding. UV-Vis spectrophotometry at 510 nm was used to perform adsorption tests at contact periods of 15–60 minutes. In comparison to both Spirulina alone (44.920%) and unmodified BFA (37.038%), the immobilized BFA–Spirulina composite had the best Fe³⁺ removal effectiveness (51.571% at 60 minutes). Synergistic interactions within the composite are responsible for this enhanced performance: Spirulina offers chemically active sites for complexation and electrostatic interactions with Fe³⁺, while BFA enhances physical adsorption and diffusion through its porous matrix. The outcomes show that the BFA–Spirulina composite is an efficient, affordable, and eco-friendly biosorbent that may be used to remediate laboratory waste that contains iron. By converting biological and agricultural wastes into valuable resources for environmental repair, this method also promotes waste valorization.